Stakeholders Engaged in Creating Sustainable Value (CVS) and Innovation (Global Journal of Management and Business Research, 2020)
This paper aims to how the creation a sustainable value network occurs and preserve valuable knowledge and innovation through stakeholder engagement. The work proceeds a qualitative study and a literature review. Finally, organizations seek to interact in a competitive environment, and through the model of Sustainable value of Hart and Milstein, the innovation and the parties concerned, respectively, with the central point generating shareholder values. The research concludes that the engagement of stakeholders in innovative sustainable organizations plays important role in the generation of value, environmental awareness, and, the implementation of the economic, environmental, and social dimensions, economic development, financial and operational. Therefore, the main contribution of this study derives from the discussion of the model of Hart and Milstein, the innovation and the parties concerned, respectively, with the central point generating stakeholder's values.
Keywords: stakeholders; innovation and creating sustainable value stakeholders engaged in creating sustainable value (CVS) and innovation